2004
DOI: 10.1093/aje/kwh083
|View full text |Cite
|
Sign up to set email alerts
|

Association between Initial Disease Presentation, Lung Disease Outcomes, and Survival in Patients with Cystic Fibrosis

Abstract: This US study was conducted to determine whether mode of diagnosis and initial disease presentation influence lung disease and survival in patients with cystic fibrosis. The study population included 27,703 patients reported to the 1986-2000 Cystic Fibrosis Foundation Registry. Patients were segregated into four diagnostic categories: meconium ileus (MI), prenatal/neonatal screening (SCREEN), positive family history (FH), and symptoms other than meconium ileus (SYMPTOM). When compared with patients in the SCRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
5
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 36 publications
3
112
5
8
Order By: Relevance
“…Individuals who are diagnosed with CF through NBS have improved nutritional status, 17 better growth, 14 and fewer hospitalizations, [17][18][19] whereas a delayed diagnosis can result in significant cognitive dysfunction 20 and nutritional failure. 4 NBS has been shown to decrease the risk of life-threatening complications 21 or death 21,22 from CF in infancy or early childhood. Families of those with CF also benefit substantially from CF NBS, because they avoid the average 15-month delay between onset of symptoms and diagnosis 17 along with the accompanying anxiety, frustration, and emotional distress.…”
mentioning
confidence: 99%
“…Individuals who are diagnosed with CF through NBS have improved nutritional status, 17 better growth, 14 and fewer hospitalizations, [17][18][19] whereas a delayed diagnosis can result in significant cognitive dysfunction 20 and nutritional failure. 4 NBS has been shown to decrease the risk of life-threatening complications 21 or death 21,22 from CF in infancy or early childhood. Families of those with CF also benefit substantially from CF NBS, because they avoid the average 15-month delay between onset of symptoms and diagnosis 17 along with the accompanying anxiety, frustration, and emotional distress.…”
mentioning
confidence: 99%
“…Similarly, in both the French study and the UKCFD analysis, no differences in lung function were identified between S and non-S cohorts (87,91). Analyses of CFNPR data likewise have found no clear evidence of a benefit of newborn screening or early asymptomatic detection in terms of lung function (26,93). † † Chest radiograph and clinical scores.…”
Section: Pulmonary Outcomesmentioning
confidence: 96%
“…However, this finding was based on less reliable data on diagnosis type from births occurring during the period before screening was widely available; no significant difference in survival between those detected through screening and those detected by symptoms other than meconium ileus was identified among those who received a diagnosis after 1986 (92,93).The survival curves were almost identical between the screened and symptomatic-detection post-1986 diagnosis groups through age 14 years. The analysis does not provide evidence of improved child survival through screening.…”
Section: Patient-oriented Outcomes Survivalmentioning
confidence: 96%
See 2 more Smart Citations